Characterization of Diazotrophs associated with roots of Leptochloa fusca (L) Kunth - Hasnain, Shahida; Zafar, Fehra; Bilal, Rakhshanda; A. Malik, Kausar (Universiti Putra Malaysia Press, 1993)
A group of nine diazotrophs were isolated from the rhizosphere of kallar grass and cultured on nitrogent-jree medium. K 5 , Ks' K9' KlD' Kl2, K13 showed high nitrogenase activity (> 18 n mol C#4 h-I viatl) whereas in K7 and K14 it was comparatively low « 5n mol C#4 h l viatl ). Maximum nitrogenase activity was found in young cultures (after 24 hours of incubation) except for K9 and Kl3 where it was maximum after 36 and 48 h, respectively. All strains were Gram-negat, produced smooth colonies and pellicles on semi-solid media. Cells of K5, K7' KID' KlI, Kl2 and K14 were pleiomorphic: Ks formed long fine rods; K9 was small, round or oval shaped; while KI4 formed beaded rods. Only Ks' K 13 and KI4were found to be motile. All isolates were able to reduce nitrate, and were positive for oxidase an catalese. None of them could denitrify or had urease activity except for K14 which was urease positive. Ks' Kl3 and KI4 were fermentative and produced red pigments. The isolates K5, KIO and KI2 are assigned to the genus Azotobacter while others remained unidentified.